Mystery Science Theater 3000 presents. 12 to the moon [videorecording (DVD)]. - Hodgson, Joel, 1960-; Nelson, Michael J.; Murphy, Kevin, 1956-; Corbett, Bill, 1960- (Shout Factory, 2016)
An international collection of astronauts reaches the moon only to discover a race of underground dwellers who seek peace by threatening violence. Also includes one short film.